2021
DOI: 10.1051/aacus/2021034
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities of inverse scheme for acoustic source localization at low frequencies

Abstract: We present the capabilities of a recently developed inverse scheme for source localization at low frequencies within an arbitrary acoustic environment. The inverse scheme is based on minimizing a Tikhonov functional matching measured microphone signals with simulated ones. We discuss the sensitivity of all involved parameters, the precision of geometry and physical boundary modeling for the numerical simulation using the finite element (FE) method, and the automatic determination of the positions of the record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…The temperature was about 26°C, the relative humidity 30%, and the atmospheric pressure was 98 kPa during the calibration and measurement. The microphones were calibrated according to the procedure described in [44]. The EDF is mounted at a fixed location inside a measurement room.…”
Section: Operation Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature was about 26°C, the relative humidity 30%, and the atmospheric pressure was 98 kPa during the calibration and measurement. The microphones were calibrated according to the procedure described in [44]. The EDF is mounted at a fixed location inside a measurement room.…”
Section: Operation Conditionmentioning
confidence: 99%
“…The acoustic properties of the facility limit the reliable experiments to frequencies above 300 Hz [45]. The room was characterized by reverberation time measurements in [5,44].…”
Section: Operation Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sound propagation models based on numerical simulation allow more complex geometrical setups. A source localization method using Finite Element simulation on two-and three-dimensional geometries is presented by Kaltenbacher, Kaltenbacher & Gombots in [26,15].…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to consider acoustic problems in the low frequency range. In numerical 2D and 3D setups it can be shown that the method improves sound source localization at low frequencies [16,17]. Additionally, in [18], the Green's functions from the FEM have been used directly to calculate the steering vectors for numerical beamforming.…”
Section: Introductionmentioning
confidence: 99%